Fiscal Decentralisation and Local Government Financing in Serbia and Montenegro - Kmezić, Sanja (Intergovernmental Fiscal Relations, 2016)
This book focuses on the fiscal decentralisation processes and the systems of local government financing in Serbia and Montenegro in the period 2000-2015. The retrospective analysis of the decentralisation processes in both countries show that they have been moving back and forth between decentralisation and centralisation, constantly swinging the pendulum of political discourse and the legal framework on intergovernmental fiscal governance. During the observed period, the systems of local government financing in both countries have often undergone drastic changes. Thus, this study focuses on the analysis of the impact of the legal framework related to intergovernmental fiscal relations, fiscal decentralisation and local government financing in Serbia and Montenegro on local government budgets. By applying both normative and economic analyses, as well as both quantitative and qualitative research methods, the study evaluates the legal quality and economic and factual effects of relevant legislation on local government budgets and status in the period 2000-2015. The study is divided into four parts: 1) Introduction; 2) Case Study: Serbia; 3) Case Study: Montenegro (both case studies include normative, economic and empirical analyses of the fiscal decentralisation process and the system of local government financing); 4) Comparative conclusions and recommendations.